2004
DOI: 10.1161/01.res.0000141528.54850.bd
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles for the Fas/Fas Ligand System in Postinfarction Ventricular Remodeling and Heart Failure

Abstract: Abstract-In myocardial infarction (MI), granulation tissue cells disappear via apoptosis to complete a final scarring with scanty cells. Blockade of this apoptosis was reported to improve post-MI ventricular remodeling and heart failure. However, the molecular biological mechanisms for the apoptosis are unknown. Fas and Fas ligand were overexpressed in the granulation tissue at the subacute stage of MI (1 week after MI) in mice, where apoptosis frequently occurred. In mice lacking functioning Fas (lpr strain) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 34 publications
7
76
0
1
Order By: Relevance
“…23,24 Recently, we reported that blockade of myofibroblast apoptosis by the treatment with pan-caspase inhibitor or with soluble Fas, a competitive inhibitor of Fas, attenuates postinfarction ventricular remodeling and heart failure. 25,26 We speculate that the preserved myofibroblasts may contribute structurally to the thickening of the infarct scar. In addition, although the property of contractile function of these myofibroblasts has not been elucidated, it is conceivable that contractile myofibroblasts that are running parallel with the infarct circumference may shrink the infarct into coronal directions and increase the infarct thickness.…”
Section: Mechanisms Of Beneficial Effects Of St␤rii On Postinfarctionmentioning
confidence: 93%
“…23,24 Recently, we reported that blockade of myofibroblast apoptosis by the treatment with pan-caspase inhibitor or with soluble Fas, a competitive inhibitor of Fas, attenuates postinfarction ventricular remodeling and heart failure. 25,26 We speculate that the preserved myofibroblasts may contribute structurally to the thickening of the infarct scar. In addition, although the property of contractile function of these myofibroblasts has not been elucidated, it is conceivable that contractile myofibroblasts that are running parallel with the infarct circumference may shrink the infarct into coronal directions and increase the infarct thickness.…”
Section: Mechanisms Of Beneficial Effects Of St␤rii On Postinfarctionmentioning
confidence: 93%
“…Surviving mice gradually develop HF within the 4 weeks following the surgical procedure [76,155,158]. In rats, a significant decrease up to 25% in cardiac output is observed 8 weeks after LAD ligation [115].…”
Section: Myocardial Infarction-induced Hfmentioning
confidence: 99%
“…13,14 Granulation tissue formed after myocardial infarction (MI) contains chronic inflammatory cells, and in recent studies, the activated Fas/FasL system and elevated levels of TNF-α released from inflammatory cells contributed to LV remodeling after AMI. 15,16 Interestingly, in our previous report we suggested that granzyme B plays an important role in triggering ACS by degrading coronary plaques, 17 amd we hypothesized that apoptosis-related molecules contribute to LV remodeling after AMI by inducing apoptosis and matrix degradation. In the present study, we focused on the role of granzyme B in LV remodeling after AMI.…”
mentioning
confidence: 90%